Watching the clock: endoplasmic reticulum-mediated control of circadian rhythms in cancer. (June 2014) - Pluquet, Olivier; Dejeans, Nicolas; Chevet, Eric
Abstract In the past 20 years both the circadian clock and endoplasmic reticulum (ER) stress signaling have emerged as major players in oncogenesis and cancer development. Although several lines of evidence have established functional links between these two molecular pathways, their interconnection and the subsequent functional implications in cancer development remain to be fully characterized. Herein, we provide an extensive review of the literature depicting the molecular connectivity linking ER stress signaling and the circadian clock and elaborate on the potential use of these functional interactions in cancer therapeutics.